Design, synthesis and biological evaluation of soluble 2,5-diketopiperazines derivatives as potential antifouling agents - Liao, Shengrong; Xu, Ying; Tang, Yong; Wang, Junfeng; Zhou, Xuefeng; Xu, Liang; Liu, Yonghong (RSC advances, 2015)
A small library of soluble 2,5-diketopiperazine derivatives were designed, synthesized and evaluated as antifouling agents against two species of marine organisms: Balanus amphitrite and Bugula neritina by larval attachment assay. The results showed that different derivatives had different antifouling activities. Among these compounds, 3a (EC 50 = 2.5 μg mL −1 ), 3b (EC 50 = 3.2 μg mL −1 ) and 3d (EC 50 = 1.6 μg mL −1 ) had strong activities, and 2d (EC 50 = 20.5 μg mL −1 ), 3l (EC 50 = 25.0 μg mL −1 ) and 3m (EC 50 = 18.5 μg mL −1 ) had moderate activities against Balanus amphitrite , but other compounds had no activities. Differently, compounds 3d (EC 50 = 3.1 μg mL −1 ) and 3i (EC 50 = 2.3 μg mL −1 ) exhibited strong activities, and 3a (EC 50 = 11.3 μg mL −1 ) and 3c (EC 50 = 17.2 μg mL −1 ) showed moderate activities against Bugula neritina , whereas other compounds had no activities. All of the active compounds had stronger antifouling activities than those of the natural product cyclo-( l -Phe- l -Pro). Compound 3d could be a new template molecule for further development as an antifouling agent because of its strong inhibitory activities against both species of fouling organisms with low or no toxicity to the environment.